Carbon Stocks Estimate of Padang City West Sumatra Province - Triyatno, Triyatno (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The most fundamental problem in this research is land cover change into settlement area and open land that occurred are high in Padang City, so the forest has reduced. If cover land of forest reduced, while population, industry and transportation growth increase the environmental gap due to plants absorbing emissions released by human activity is reduced. As a result the surface temperature becomes warmer. If this is left continuously, the hydrometeorology disaster will threaten Padang City. In general, this research aims to determine how the phenomenon of climate change that occurred in Padang City based on the estimation of carbon stocks in accordance with land cover. Analysis of the occurrence of climate change can be known based on the tendency of temperature data and rainfall data contained in Padang City. In addition, climate change can be analyzed based on changes in land cover and carbon stocks. Based on the result, it is known that Padang City since 1989 experienced considerable changes, especially changes from forest to settlements and mixed land. That land cover changes, indirectly cause the carbon stocks of Padang City also decreased. This is because other land cover rather than forests have low carbon stocks, especially settlements and open land that do not have carbon stock. Carbon stocks reduced, it is assumed to cause increasing air temperature and reducing rainfall.